Analysis of Inflation in Poland in 2019-2023 And Its Impact on Management and Finance in A Companies - Iwona PRZYCHOCKA (Communications of International Proceedings, 2023)
In the article entitled Analysis of the phenomenon of inflation in Poland in 2019-2023 and its impact on management and finance in the enterprise, the analysis of the issue undertaken and it was shown that the phenomenon of inflation affects the management in companies. The above-mentioned problem undertaken due to the changing market conditions and thus the functioning of market entities in such difficult market conditions that have never existed before. The aim of the article was to analyze inflation and show how it affects management and finance in enterprises. In 2019, it was not assumed that in the coming years will come to face pandemic, war and inflation. The article presented here characterizes inflation, its causes, effects. It was shown how inflationary changes took place in the era of the pandemic and then war in Ukraine. It was shown how the financial situation of companies was shaped, which companies lost and which gained in the era of the pandemic and war. Undoubtedly, the outbreak of the pandemic and war, as well as high inflation in the 1920s, are the most significant and traumatic events of this century. The effects of these phenomena will still be felt for years to come. The article uses a wealth of literature on the subject, including an electronic source as the most current source of information. The article uses analysis and observation as research methods.
Keywords: inflation; enterprise; finance; management; basket of goods